Prostate Cancer Therapy Using Docetaxel and Formononetin Combination: Hyaluronic Acid and Epidermal Growth Factor Receptor Targeted Peptide Dual Ligands Modified Binary Nanoparticles to Facilitate the in vivo Anti-Tumor Activity - Dong Z; Wang Y; Guo J; Tian C; Pan W; Wang H; Yan J (Dove Medical Press, 2022)
Zhaoqiang Dong,1 Yuzhen Wang,2 Jing Guo,3 Chuan Tian,4 Wengu Pan,4 Hongwei Wang,4 Jieke Yan4 1Department of Cardiology, The Second Hospital of Shandong University, Ji'nan, 250033, People's Republic of China; 2Clinical Department, Jinan Vocation College of Nursing, Ji'nan, 250033, People's Republic of China; 3Department of Gynaecology, The Second Hospital of Shandong University, Ji'nan, 250033, People's Republic of China; 4Department of Renal Transplantation, The Second Hospital of Shandong University, Ji'nan, 250033, People's Republic of ChinaCorrespondence: Jieke Yan, Department of Renal transplantation, The Second Hospital of Shandong University, No. 247 Beiyuan Street, Ji'nan, 250355, People's Republic of China, Email yanjiekesdu@163.comObjective: To evaluate the prostate cancer therapy efficiency of the synergistic combination docetaxel (DTX) and formononetin (FMN) in one nano-sized drug delivery system. Hyaluronic acid (HA) and epidermal growth factor receptor-targeted peptide (GE11) dual ligands were applied to modify the nano-systems.Methods: In this study, GE11-modified nanoparticles (GE-NPs) were applied for the loading of DTX, and HA-decorated NPs (HA-NPs) were used to encapsulate FMN. HA and GE11 dual ligand-modified binary nanoparticles (HAGE-DTX/FMN-NPs) were constructed by the self-assembling of GE-NPs and HA-NPs. The anti-PCa ability of the system was evaluated in vitro on PC-3 human prostate carcinoma cells (PC3 cells) and in vivo on PC3 tumor-bearing mice in comparison with single NPs and free drugs formulations.Results: HA/GE-DTX/FMN-NPs were nano-sized particles with smaller particles coating on the inner core and achieved a size of 189.5 nm. HA/GE-DTX/FMN-NPs showed a cellular uptake efficiency of 59.6%, and a more efficient inhibition effect on PC3 cells compared with single ligand-modified NPs and free drugs. HA/GE-DTX/FMN-NPs showed significantly higher tumor inhibition efficiency than their single drug-loaded counterparts and free drugs.Conclusion: HA/GE-DTX/FMN-NPs have a synergistic anti-tumor effect and also could the reduce unexpected side effects during the cancer therapy. It could be used as a promising anti-PCa system.Keywords: prostate cancer, docetaxel, formononetin, hyaluronic acid, epidermal growth factor receptor, binary nanoparticles